Implementation of Tolerance Character Education: a Comparative Study of Indonesian and Danish Elementary Schools - Prihastanti, Erika; Hidayat, Muhamad Taufik (Universitas Muhammadiyah Surakarta, 2023)
Purpose: The purpose of this research is to analyse and compare the implementation of tolerance character education, which consists of elements of appreciation and respect, recognising rights, and providing freedom in elementary schools in Indonesia and Denmark. Methodology: This research employs a descriptive qualitative approach with a comparative literature review design. The methodology involves searching for relevant data sources and sorting the gathered information. Data analysis comprises collecting, reducing, presenting, and drawing conclusions from the data. The author employs various validation techniques to ensure data validity, including check and recheck methods, collaboration with other researchers, and source triangulation. Results: The research findings reveal several key points: (1) in both Indonesia and Denmark, tolerance education is implemented through various methods, including debate learning activities, religious education, students' freedom to celebrate holidays, active group discussions, and role-playing activities. (2) in Indonesia, tolerance is particularly emphasised within citizenship education. Additionally, it is integrated into daily habits such as praying and shaking hands, cultural tourism visits, and literacy activities. (3) conversely, in Denmark, the implementation of tolerance character education places a strong emphasis on direct experiential learning. This involves presenting examples of concrete problems and teaching the concept of hygge living, which promotes living together peacefully by engaging in simple activities that foster respect and harmony. Applications/Originality/Value: This research undertakes a comparative analysis of tolerance character education in Indonesian and Danish elementary schools through a literature review study method.